コクリツキョクチケンキュウジョ ノ サイエンス・データマネージメント ニ カンスル ワークショップ ホウコク - 福地, 光男; フクチ, ミツオ; Belbin, Lee; Watts, David; 平譯, 享; ヒラワケ, トオル; Fukuchi, Mitsuo; Hirawake, Toru (2005)
P(論文) 2004年2月25-27日に国立極地研究所にて,「国立極地研究所のサイエンス・データマネージメントに関するワークショップ」が開催された.南極研究科学委員会と南極観測実施責任者評議会により設立された「合同南極データマネージメント委員会」において主導的な活動をしてきたオーストラリア南極局のデータマネージャー等2名を招待し,南極局におけるおよそ過去10年におけるデータマネージメントの発展をレビューし,国立極地研究所におけるデータマネージメントの今後の方向性について討議した. The Workshop on Science Data Management was held at the National Institute of Polar Research (NIPR) from February 25-27, 2004. The Manager and Senior Applications developer from the Australian Antarctic Data Centre (AADC) were invited to distil the development and operation of the AADC in the context of Antarctic science data management and the Joint Committee on Antarctic Data Management (JCADM). The current data management situation and future requirements at NIPR were identified. departmental bulletin paper